2018
DOI: 10.1007/s11657-018-0498-5
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal concentrations of perfluoroalkyl substances and bone health in British girls at age 17

Abstract: Prenatal concentrations of some PFAS may be associated with reduced bone mass and size in adolescent girls, although it is not clear whether these associations are driven by body size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…In the same cohort, maternal plasma PFUnDA and PFHxS concentrations have been significantly associated with decreased neonatal thigh length at birth [ 8 ]. Studies have shown associations between prenatal exposure to PFAS and bone development [ 42 , 43 ]. Our findings may point to potential pathway through placenta DNA methylation; however, the mediation analysis results were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…In the same cohort, maternal plasma PFUnDA and PFHxS concentrations have been significantly associated with decreased neonatal thigh length at birth [ 8 ]. Studies have shown associations between prenatal exposure to PFAS and bone development [ 42 , 43 ]. Our findings may point to potential pathway through placenta DNA methylation; however, the mediation analysis results were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…2016 ). Bone acquisition begins before birth ( Harrast and Kalkwarf 1998 ), but few human studies have evaluated the influence of environmental chemical exposures during gestation on bone accrual and strength later in life ( Jeddy et al. 2018 ; van Zwol-Janssens et al.…”
Section: Introductionmentioning
confidence: 99%
“…2019 ). In a prospective study of PFAS exposures during pregnancy, higher maternal serum PFAS concentrations were associated with lower whole-body bone mineral content (BMC), areal BMD (aBMD), and bone area among 17-y-old females ( Jeddy et al. 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, experimental and human autopsy evidence suggests accumulation of PFAS in the skeleton [11][12][13] . Epidemiological studies have reported an inverse relationship between PFAS exposure and bone health [14][15][16][17][18][19] , suggesting a possible role of PFAS in the onset of osteoporosis, however the associated mechanisms are still unexplored. Because different PFASs, including PFOA, have been associated with altered sex steroid 20,21 and thyroid hormone levels [22][23][24] we hypothesized that they may also affect vitamin D metabolism.…”
mentioning
confidence: 99%